Extracurricular Students' Lob Shot Accuracy was Improved by Drilling Training and Patterned Strokes Method - Mochamad Reza Aditiya Maskun; Khaeroni Khaeroni; Iwan Setiawan (Musamus Journal of Physical Education and Sport (MJPES), 2023)
Objectives. The purpose of this research is to investigate the impact of drilling methods and patterned strokes on the precision of students' lob shots in badminton. By identifying the most effective training methods, badminton extracurriculars can create more focused and effective training programs. This research is unique in its emphasis on accuracy in lob shots, rather than simply precision of movement as in previous studies. Materials and methods. This study employs a comparative quantitative approach that utilizes an experimental method with a Two-group pretest-posttest Design to investigate the lob hit accuracy of badminton players. The research was conducted at Padindi Vocational School, West Jakarta, with a sample size of 20 students who participated in the badminton extracurricular. The total sampling technique was used to divide the participants into two distinct treatment groups, with 10 individuals in the group that used the drilling drill method and the other 10 in the group that employed the patterned strokes method. The obtained data on lob hit accuracy was collected through test instruments. Results. Based on the results of the Independent Sample T-Test, it can be concluded that the drilling training method is more effective than the patterned strokes training method in improving the accuracy of lob shots. The t count obtained from the test was 2.425, which is higher than the t table value of 2.10092. Conclusion. The research study found that both the drilling training method and the patterned strokes training method had a positive impact on improving the accuracy of lob shots. The average score before the training for the drilling method was 6.40 which increased to 8.60 after the training. Similarly, for the patterned strokes training method, the average pretest score was 6.70 which improved to 7.20 after the training. These findings suggest that both of these training methods can be effective in enhancing the accuracy of lob shots.